2007
DOI: 10.1007/s00442-007-0823-y
|View full text |Cite
|
Sign up to set email alerts
|

Resource distribution influences mating system in the bobuck (Trichosurus cunninghami: Marsupialia)

Abstract: Mammalian mating systems are thought to be shaped by the spatial distribution and abundance of key resources, which in turn influence the spacing behaviour of individuals. In particular, female home range size is predicted to reflect the availability of key resources. We documented the availability and distribution of food and shelter resources for two neighbouring populations of bobucks, or mountain brushtail possums, Trichosurus cunninghami, that were characterised by different mating systems: our "forest po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 47 publications
(69 reference statements)
1
39
0
Order By: Relevance
“…Because mountain ash trees are the only trees at this site large enough to form hollows suitable for mountain brushtail possums, the varying age of the mountain ash overstorey results in spatial heterogeneity in the availability of den resources (figure 1). Mountain brushtail possums are predominantly solitary, although they occasionally share dens with other individuals and a proportion of individuals form 'socially monogamous' pairs, the rate of which varies between populations [31,33]. At our Cambarville study site, the rate of sequential (between years) monogamy was approximately 46 per cent for females and 60 per cent for males, which is higher than expected random mating (M. D. J. Blyton, S. C. Banks, D. B. Lindenmayer & R. Peakall 2010, unpublished data).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because mountain ash trees are the only trees at this site large enough to form hollows suitable for mountain brushtail possums, the varying age of the mountain ash overstorey results in spatial heterogeneity in the availability of den resources (figure 1). Mountain brushtail possums are predominantly solitary, although they occasionally share dens with other individuals and a proportion of individuals form 'socially monogamous' pairs, the rate of which varies between populations [31,33]. At our Cambarville study site, the rate of sequential (between years) monogamy was approximately 46 per cent for females and 60 per cent for males, which is higher than expected random mating (M. D. J. Blyton, S. C. Banks, D. B. Lindenmayer & R. Peakall 2010, unpublished data).…”
Section: Methodsmentioning
confidence: 99%
“…At our Cambarville study site, the rate of sequential (between years) monogamy was approximately 46 per cent for females and 60 per cent for males, which is higher than expected random mating (M. D. J. Blyton, S. C. Banks, D. B. Lindenmayer & R. Peakall 2010, unpublished data). Females produce a single offspring per year [33].…”
Section: Methodsmentioning
confidence: 99%
“…The highly skewed use of sleeping sites suggests that sleeping site trees are restricted in the study area and may thus represent a limiting resource for female grey mouse lemurs as has been reported for other mammals (e.g. Du Plessis 1992; Doncaster & Woodroffe 1993;Martin & Martin 2007;Walker et al 2007). The importance of large trees for the study species is further indicated by the uneven distribution of grey mouse lemurs in the study area that has previously been linked to vegetation features such as a lack of large trees and cover with plant creepers (Rendigs et al 2003).…”
Section: Sleeping Sites As Limiting Resourcementioning
confidence: 94%
“…Day & Elwood 1999;Sedgeley & O'Donnell 1999;Martin & Martin 2007). In addition, the availability of suitable sleeping sites can limit population density and affect a species' space use and social interactions (Du Plessis 1992;Doncaster & Woodroffe 1993;Chaverri et al 2007b;Martin & Martin 2007;Walker et al 2007;Kerth 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation